" The Third Language 'in-between' in the Novels of Ahmed Youssef Dawood" (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Language is one means of communication that has the most significant role in enhancing humans' life and their relation with their environment alongside their relations with the society in which they were born and raised. Language has always been the product of this society on whose progress and regress have an impact upon it. It is well-known that standard Arabic is the official language with its accurate grammar and vocabulary moving from the ancestor to the descendant. However, it very often may be difficult to apply or have access to for most people regardless of their cultural qualifications. It is also difficult for this language to convey or transfer reality as clear as it is or to express how easy and spontaneous life is to all people. Since the phenomenon of vernacular language alongside standard language is a linguistic one all over the world, thus the necessity in the Arabic novel in general and countryside in particular emerged to have an in-between third language that is neither standard nor vernacular. This novel language is to be capable of bringing the standard closer to daily life and ending up with one form of dialogue that provides characters with their psychological and social traits; a tacit language for all different cultural and scientific levels of readers and their social status. Also, this language will help the text express the human emotions that emerge subconsciously for the standard one is incapable of doing so. Needless  to say, standard Arabic was one day a vernacular with different dialects expressed through words like "language" and "tongue." Allah said: ("We have not sent but a messenger to represent his nation and clarify the truth to them. For, God guide and misguide whomsoever thus He is the Noble and Wise").* - أستاذ – قسم اللغة العربيّة – كليّة الآداب والعُلوم الإنسانيّة – جامعة تشرين – اللاذقيّة سورية.** - طالبة ماجستير (الدراسات الأدبيّة) – قسم اللغة العربيّة – كليّة الآداب والعُلوم الإنسانيّة – جامعة تشرين – اللاذقيّة – سورية.[1] - القرآن الكريم، سورة إبراهيم، الآية (4).